Interaction of Ultrathin Films of Ethylene Carbonate with Oxidized and Reduced Lithium Cobalt Oxide—A Model Study of the Cathode|Electrolyte Interface in Li‐Ion Batteries. Issue 3 (18th December 2018) - Buchner, Florian; Fingerle, Mathias; Kim, Jihyun; Späth, Thomas; Hausbrand, René; Behm, R. Jürgen
Abstract: Aiming at a detailed, molecular‐scale understanding of the initial stages of the solid|electrolyte interphase (SEI) formation in Li‐ion batteries, the interaction of the common electrolyte solvent component ethylene carbonate (EC) with fully lithiated LiCoO2 and reduced LiCoO2− δ films as model electrodes for the cathode is investigated. The results are compared with previous findings for pristine and lithiated highly oriented pyrolytic graphite, serving as model anode. Employing X‐ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy measurements, it is found that vapor deposition of EC on LiCoO2 and LiCoO2− δ at 80 K results in molecularly adsorbed EC, both in the monolayer and in the multilayer regime. XPS measurements detect significant changes of the adlayer between 170 and 255 K, indicating competing desorption and decomposition. Synchrotron‐based XPS measurements reveal a very similar decomposition pattern upon EC deposition on LiCoO2 at close to ambient temperatures. In both cases, the remaining adlayer is mostly composed of Li‐containing CO, COC, CH, and CC moieties such as Li2 CO3, ROCO2 Li, (CH2 OCO2 Li)2, and Li2 O2 . The activated decomposition of EC is caused by interaction with the oxide surface or, more specifically, with surface Li. This process can be considered as the initial stage of the chemical SEI formation. Abstract : Aiming towards a molecular‐scale understanding of the formation of the solid|electrolyte interphase at the electrode|electrolyte interface in Li‐ion batteries, the interaction of ethylene carbonate (electrolyte/solvent) with LiCoO2 films (model for the cathode) is explored, employing X‐ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy under ultrahigh‐vacuum conditions.